Music as engaging, educational matrix: Exploring the case of marginalised students attending an "alternative" music industry school. (December 2014) - Cleaver, David; Riddle, Stewart
Harmony High is an alternative school where music functions as an educational magnet to attract marginalised students who have disengaged from the mainstream. Through an investigation of the student perspective, we discover that while acting as a magnet, music also becomes the educational matrix or "heart and soul" that helps to create a school culture with a positive spirit of connectedness and community working to motivate and inspire active learning. Thus Harmony High demonstrates a model highlighting the need for alternative education contexts that adapt to the needs, voice, interests and experiences of disaffected students. This becomes increasingly important in order to offer alternatives to current neoliberal agendas that focus on the standardisation of education in order to meet economic political and market ideals rather than the needs of students.